2021
DOI: 10.1101/2021.11.18.21266480
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

KBG Syndrome: Prospective Videoconferencing and Use of AI-driven Facial Phenotyping in 25 New Patients

Abstract: Genetic variants in the gene Ankyrin Repeat Domain 11 (ANKRD11) and deletions in 16q24.3 are known to cause KBG syndrome, a rare syndrome associated with craniofacial, intellectual, and neurobehavioral anomalies. We report 25 unpublished individuals from 22 families, all with molecularly confirmed diagnoses of KBG syndrome. Twenty-one individuals have de novo variants, three have inherited variants, and one is inherited from a parent exhibiting low-level mosaicism. Of these variants, 20 are truncating (framesh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…A separate written informed consent was obtained for publication of photographs; these photos were loaded onto Face2Gene (version 20.1.4; FDNA Inc, USA) (Gurovich et al 2019) and GestaltMatcher (version 1.0) through Bonn University (Hsieh et al 2022). Future work will focus on detailed analysis of the many photographs with these programs that use deep convolutional neural networks to build syndrome and patient classifiers, respectively, as we recently accomplished for a different syndrome, KBG Syndrome (Guo et al 2021).…”
Section: Methodsmentioning
confidence: 99%
“…A separate written informed consent was obtained for publication of photographs; these photos were loaded onto Face2Gene (version 20.1.4; FDNA Inc, USA) (Gurovich et al 2019) and GestaltMatcher (version 1.0) through Bonn University (Hsieh et al 2022). Future work will focus on detailed analysis of the many photographs with these programs that use deep convolutional neural networks to build syndrome and patient classifiers, respectively, as we recently accomplished for a different syndrome, KBG Syndrome (Guo et al 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Although there were differences in the degree of delay among the patients included in this study, developmental delay or intellectual disability was observed in all eight patients, consistent with previous findings. The reported co‐occurrence rate of ADHD and KBG syndrome is generally10–15% (Goldenberg et al, 2016 ; Low et al, 2016 ), while one paper proposed a rate of approximately 28% (Guo et al, 2021 ). Of the eight patients in this study, two were diagnosed with ADHD, representing 25% comorbidity; however, continued follow‐up is required, as this study included infants who are not yet of an age at which ADHD can be tested.…”
Section: Discussionmentioning
confidence: 99%
“…Data collected from 25 of these individuals has already been published. 12 The individuals interviewed reside in 11 different countries and were recruited via a private Facebook group created by the KBG Foundation or by self-referral. Inclusion criteria included a molecular diagnosis of KBG syndrome, which was confirmed by review of medical records by G.J.L.…”
Section: Methodsmentioning
confidence: 99%